Influence of age, spatial memory, and ocular fixation on localization of auditory, visual, and bimodal targets by human subjects - Dobreva, Marina S.; O’Neill, William E.; Paige, Gary D. (Experimental brain research, 2012)
A common complaint of the elderly is difficulty identifying and localizing auditory and visual sources, particularly in competing background noise. Spatial errors in the elderly may pose challenges and even threats to self and others during everyday activities, such as localizing sounds in a crowded room or driving in traffic. In this study, we investigated the influence of aging, spatial memory, and ocular fixation on the localization of auditory, visual, and combined auditory–visual (bimodal) targets. Head-restrained young and elderly subjects localized targets in a dark, echo-attenuated room using a manual laser pointer. Localization accuracy and precision (repeatability) were quantified for both ongoing and transient (remembered) targets at response delays up to 10 s. Because eye movements bias auditory spatial perception, localization was assessed under target fixation (eyes free, pointer guided by foveal vision) and central fixation (eyes fixed straight ahead, pointer guided by peripheral vision) conditions. Spatial localization across the frontal field in young adults demonstrated (1) horizontal overshoot and vertical undershoot for ongoing auditory targets under target fixation conditions, but near-ideal horizontal localization with central fixation; (2) accurate and precise localization of ongoing visual targets guided by foveal vision under target fixation that degraded when guided by peripheral vision during central fixation; (3) overestimation in horizontal central space (±10°) of remembered auditory, visual, and bimodal targets with increasing response delay. In comparison with young adults, elderly subjects showed (1) worse precision in most paradigms, especially when localizing with peripheral vision under central fixation; (2) greatly impaired vertical localization of auditory and bimodal targets; (3) increased horizontal overshoot in the central field for remembered visual and bimodal targets across response delays; (4) greater vulnerability to visual bias with bimodal stimuli. Results highlight age-, memory-, and modality-dependent deterioration in the processing of auditory and visual space, as well as an age-related increase in the dominance of vision when localizing bimodal sources.